Motivation and job satisfaction of Nursing staff at the San Francisco Support Hospital, Ayacucho-2018 - Montes Salcedo, Marleny (2020)
Objective: Of determining the relationship that exists between the degree of motivation and the level of job satisfaction of the nursing staff working in the Hospital of Support San Francisco Ayacucho, 2018. Methodology: Has a focus quantitative and correlational type, non-experimental design. Instrument: to assess the motivation variable was worked by Hackman and Oldham (1974), and to evaluate job satisfaction the SL-SPC scale was used, verified by the psychologist Sonia Palma, both instruments were applied to 50 people representing the nursing staff. Results allowed to verify that the correlation between the variable motivation and the variable of job satisfaction show a moderate and direct relationship (r = 0.488, p = 0.000), the analysis made between the variable of job satisfaction and the dimensions of the motivation showed a moderate relationship and significant in the feedback (r = 0.425, p = 0.002), and autonomy for the completion of the task (r = 0.406, p = 0.003); the importance of the task revealed a direct and significant low relation (r = 0.334, p = 0.000). Not enough evidence was found to affirm a relationship between job satisfaction and identity dimensions with the task (r = 0.251, p = 0.079) and variety of the task (r = 0.049, p = 0.736). Conclusion: That there is a moderate relationship between the variable motivation and job satisfaction. Likewise, a moderate relationship is observed between the feedback dimension and the autonomy to carry out the task.